(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
The study aimed to identify the level of scientific competence of faculty members, the level of quality of higher education at the University of Damascus, and the impact of the scientific competence of faculty members at Damascus University on the quality of higher education. The researcher adopted the descriptive analytical method based on studying correlational relationships The research sample included (8) faculties at Damascus University, including (4) theoretical and (4) applied. A sample of postgraduate students was drawn using the available sample method from each college, so the number of members of this sample reached (365) postgraduate students from the community. The original number (6126) of postgraduate students, in the selected colleges. The research tool was the questionnaire. The study showed a set of results, the most important of which were: The level of scientific competence of faculty members was high. The quality of higher education was high. It was also found that there were differences between the average scores of the research sample members regarding the level of academic competence of faculty members and the quality of higher education according to the gender variable in favor of females. There are no differences according to the type of college. The results also indicated that there is a strong correlation between the level of scientific competence and the quality of higher education, in addition to the existence of a linear relationship between the two variables, meaning that the independent variable (scientific competence) affects the dependent variable (quality of higher education).